Performance Evaluation of IPv6 Jumbogram Packets Transmission using Jumbo Frames - Supriyanto Supriyanto; Rian Sofhan; Rian Fahrizal; Azlan Osman (IAES Indonesia Section, 2017)
IPv6 is an ultimate solution to the Internet address exhaustion. It is believed, the protocol will be requested by not only human but also everything on the earth surface. Furthermore, the improvement on the protocol is important to achieve IP packets transmission efficiently. Processing technology has been improved to become very fast packet processing both in host as well as intermediate systems. The lower layer technologies have supported to transmit Gigabits data per second. However, there is a limitation on transferring large data due to the current MTU on the widely used link layer technology which is Ethernet is still 1500 bytes. This research aims to evaluate performance of IPv6 packets transmission using jumbo frames. The evaluation was done by transmitting IPv6 packets larger than 1500 bytes in Windows operating systems. The results show, transmitting larger packets size using jumbo frame can increase the network throughput by up to 117%.